Detection of intestinal parasites by different methods in our type 2 diabetic patients - Müge Özsan Yılmaz (Acta Medica Alanya)
Aim: Long term persistently high blood glucose levels result in various complications and conditions in diabetic patients. One of them is gastrointestinal disorders and the other is increased risk of infectious diseases like parasitosis. The aim of the study is to demonstrate of intestinal parasites with various techniques in diabetic patients and confirm of the frequency of the parasites.Methods: A total of 65 patients with type 2 Diabetes Mellitus were included in the study. Laboratory tests were done and gastrointestinal symptoms were recorded. Fecal specimens were evaluated with direct microscopy, Kinyoun acid-fast staining method, trichrome staining method and antigen screening test.Results: Of the patients included in the study 31 were male and 34 were female. While 53.8% of the patients had no chronic complications of diabetes, 33.8% had multiple complications. Thirty (46.2%) patients had gastrointestinal complaints. Examination of stool samples revealed G. intestinalis in two patients (3.07%), C. parvum in three patients (4.6%), and G. intestinalis + E. histolytica in six patients (9.2%) by RAT. No association was found between the existence of parasite determined by RAT and any of the patient characteristics of age, sex, duration of diabetes, and dyspeptic complaints (p-values are 0.27; 0.14; 0.90; 0.68, respectively).Conclusion: This is the first study to explore the prevalence rate of parasitosis detected by RAT in patients with diabetes. In this study, we also compared different parasite detection methods in this patient population and showed that RAT is a more sensitive method.